Sistema informático móvil para el aprendizaje de educación para la salud en la población bilingüe de la comunidad Huitoto Murui Bue “Centro Arenal” - Pereyra Trigoso, Kiper (2022)
This paper presents the results of the use of the "Curate ñañito" mobile computer system, contextualised as a tool to support health services from the perspective of providing education on health topics to indigenous populations in the Peruvian Amazon. The development and testing of the tool involved the participation of speakers from the indigenous community "Centro Arenal" located on the Nanay River near the city of Iquitos. The main objective was to implement a mobile computer system for the learning of health education in the bilingual population of the original village Huitoto Murui Bue "Centro Arenal". The research is of the Applied type, of pure experimental design. At the end of the tests, the results showed a high percentage of knowledge of the information and the acceptance of the users, so it was concluded that the use of a computer system has a greater scope and is favorable for the learning of health topics in the cultural context of the language Huitoto Murui Bue, therefore the hypothesis is accepted: "The use of the mobile computer system, will facilitate the learning of health education in the bilingual population of the native town Huitoto Murui Bue "Centro Arenal".